Synthesis, characterization and antioxidative assay of ester and amide derivates of 2,6-dimethyl-4-(substituted)-1,4-dihydropyridine-3,5-dicarboxylic acid - Tamara Mijatović; Milica Perić; Luka Matović; Marija Ristović; Saša Drmanić (Journal of Engineering & Processing Management, 2018)
Six ester and amide derivates of 2,6-dimethyl-4-(substituted)-1,4-dihydropyridine-3,5-dicarboxylic acid have been synthesized in this paper, including: diethyl 2,6-dimethyl-4-phenyl-1,4-dihydropyridine-3,5-dicarboxylate, diethyl 2,6-dimethyl-4-(3-nitrophenyl)-1,4-dihydropyridine-3,5-dicarboxylate, diethyl 2,6-dimethyl-4-(4-nitrophenyl)-1,4-dihydropyridine-3,5-dicarboxylate, diethyl 4-(2-hydroxyphenyl)-2,6- dimethyl-1,4-dihydropyridine-3,5-dicarboxylate, diethyl 4-(3-hydroxyphenyl)-2,6-dimethyl-1,4-dihydropyridine-3,5-dicarboxylate and diethyl 4-(4-hydroxyphenyl)-2,6-dimethyl-1,4-dihydropyridine-3,5-dicarboxylate. Obtained ester derivates were used afterwards as a starting compounds for synthesis of amide derivates, including: 2,6-dimethyl-4-phenyl-N3,N5-di(thiazol-2-yl)-1,4-dihydropyridine-3,5-dicarboxamide, 2,6-dimethyl-4-(3-nitrophenyl)-N3,N5-di(thiazol-2-yl)-1,4-dihydropyridine-3,5-dicarboxamide, 2,6-dimethyl-4-(4-nitrophenyl)-N3,N5-di(thiazol-2-yl)-1,4-dihydropyridine-3,5-dicarboxamide, 4-(2-hydroxyphenyl)-2,6-dimethyl-N3,N5-di(thiazol-2-yl)-1,4-dihydropyridine-3,5-dicarboxamide, 4-(3-hydroxyphenyl)-2,6-dimethylN3,N5-di(thiazol-2-yl)-1,4-dihydropyridine-3,5-dicarboxamide and 4-(4-hydroxyphenyl)-2,6-dimethylN3,N5-di(thiazol-2-yl)-1,4-dihydropyridine-3,5-dicarboxamide. Obtained compounds were characterized by melting point, elementary analysis and FT-IR spectroscopy. In order to determine the effect of the substituent, the antioxidative activity assay of obtained 1,4- dihydropyridines was performed by using the DPPH (1,1-diphenyl-2-picryl-hydrazyl) free radical scavenging method.
Keywords: 1; 4-dihydropyridines; esters; amides; antioxidative activity; DPPH; free radicals